Evaluating the student nutrition improvement program: regional disparities and nutritional trends in Yunnan, China (2019–2023) - Xu, Fang; Huang, Xin; Yu, Long; Yang, Yadi; Chang, Litao (Frontiers in Public Health, 2025)
BackgroundIn order to improve the nutrition and health status of rural school-age children and to reduce malnutrition. This study evaluated the effects of the National Nutrition Improvement Program for Rural Compulsory Education Students (NNIP-RCES) in three counties (Midu, Xuanwei, and Xundian) in Yunnan Province, China, in 2019, 2021, and 2023, and the findings highlight regional differences and future nutrition trends.MethodsAnthropometric indicators (height and weight) and biochemical markers (hemoglobin, Vitamin A, and Vitamin D) were measured and analyzed using linear mixed-effects models to identify temporal changes, regional differences, and the overall effectiveness of the program.ResultsThe program led to significant improvements in height (β = 0.42, p = 0.013), weight (β = 0.66, p < 0.001), and Vitamin A levels (β = 0.011, p < 0.001), demonstrating notable progress in physical growth and Vitamin A supplementation. However, hemoglobin levels declined significantly (β = −0.38, p = 0.005), particularly in Xundian, highlighting ongoing challenges in anemia prevention. Vitamin D levels remained stable with no significant improvements (p = 0.488), possibly influenced by factors such as limited dietary variety and seasonal variations in sun exposure. Additionally, considerable disparities in program outcomes were observed among counties, with Midu generally showing superior improvements compared to Xuanwei and Xundian.ConclusionWhile the NNIP-RCES effectively enhanced physical growth and alleviated Vitamin A deficiency, persistent anemia, unchanged Vitamin D levels, and marked regional disparities underscore critical areas requiring further attention. Future policy refinements should focus on targeted interventions addressing anemia prevention, Vitamin D supplementation, enhanced dietary diversity, and equitable resource allocation across regions. Strengthened monitoring frameworks and comprehensive nutrition education initiatives are also recommended to ensure sustainable improvements and serve as a model for global school-based nutritional interventions.